IDENTIFICATION OF ESCHERICHIA COLI AND ORGANIC SUBSTANCES BASED ON THE DISTANCE FROM THE DUG WELL TO THE SEP-TIC TANK - Brilyan Nissa, Gendis; Pujiastuti, Peni (Universitas Medan Area, 2024)
As many as 70% of drinking water sources in Indonesia are contaminated with feces which can cause the spread of diarrheal diseases. There were 1,177 cases of diarrhea spread across Colomadu District. In Pucung Village, Colomadu District, complaints about well water being colored, smelly, tasteful, slimy, and people often experiencing diarrhea, especially those located less than 10 m from the septic tank. In accordance with Minister of Health Regulation Number 32 of 2017 concerning Water Hygiene, the E. coli content is 0 CFU/100 ml and the maximum organic material content is 10 mg/l. The E. coli analysis method uses Total Plate Count (TPC) on agar plates according to SNI 2897:2008. Research needs to be carried out to ensure the quality of well water regarding the content of E. coli and organic substances. Determination of organic substance levels was carried out using the permanganometric titration method according to SNI 06-6989.22-2004. This research uses the TPC method to determine water quality and is included in qualitative research which focuses on case studies. Based on the research, the results showed that the values ​​of organic substances and E. coli in sample I were 17.20 mg/l and 1.6 x 109 CFU/100 ml, sample II was 11.88 mg/l and 5.0 x 105 CFU / 100 ml, while sample III was 6.88 mg/l and 2.3 x 104 CFU/100 ml. So, the quality of the well water in the Pucung Village studied did not meet the requirements of Minister of Health Regulation Number 32 of 2017.